PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAAN PERBANKAN, HEALTHCARE, DAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Winda Arlita; Ade Ningsih Wijaya; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This journal aims to assess the impact of financial performance on stock prices in companies within the banking, healthcare, and manufacturing sectors listed on the Indonesia Stock Exchange (BEI) during the period of 2018-2020. The study encompasses various financial performance indicators with the intent of comprehending how variables contribute to stock price fluctuations. The data analyzed is sourced from the annual financial reports of companies listed on the BEI during the research period. Through meticulous statistical analysis, this journal seeks to provide an in-depth understanding of how financial performance influences the stock value of companies in different sectors. The hope is that the findings of this research will offer valuable insights to various stakeholders, including investors, corporate management, and regulators, aiding them in making strategic decisions related to investment and risk management.